An Association of an eBURST Group With Triazole Resistance of Candida tropicalis Blood Isolates - Tulyaprawat, Orawan; Pharkjaksu, Sujiraphong; Chongtrakool, Piriyaporn; Ngamskulrungroj, Popchai (Frontiers in Microbiology, 2020)
Candidemia, a bloodstream infection caused by genus Candida, has a high mortality rate. C. albicans was previously reported to be the most common causative species among candidemia patients. However, during the past ten years in Thailand, C. tropicalis has been recovered from blood more frequently than C. albicans. The cause of this shift in the prevalence of Candida spp. remains unexplored. We conducted in vitro virulence studies and antifungal susceptibility profiles of 48 C. tropicalis blood isolates collected during 2015-2017. To compare to global isolates of C. tropicalis, multilocus sequence typing (MLST), a minimum spanning tree, and an eBURST analysis were also conducted. C. tropicalis and C. albicans were the most (47 - 48.7%) and second-most (21.5 – 33.9%) common species to be isolated from candidemia patients, respectively. Of the C. tropicalis blood isolates, 29.2%, 0%, 100%, and 93.8% exhibited proteinase activity, phospholipase activity, hemolytic activity, and biofilm formation, respectively. Moreover, 20.8% (10/48) of the isolates were resistant to voriconazole and fluconazole, and also showed high MICs to posaconazole and itraconazole. In contrast, most of the isolates were susceptible to anidulafungin (97.9%), micafungin (97.9%) and caspofungin (97.9%), and showed low MICs to amphotericin B (100%) and 5-flucytosine (100%). The MLST identified 22 diploid sequence types. Based on the eBURST analysis and minimum spanning tree, 9 out of 13 members (69.2%) of an eBURST group 3 were resistant to voriconazole and fluconazole, and also showed high MICs to posaconazole and itraconazole. Association analysis revealed the eBURST group 3 was significantly associated with the four triazole resistance (p < 0.001). In conclusion, the eBURST group 3 was associated with the triazole resistance and resistance to many antifungal drugs might be collectively responsible for the prevalence shift.